Studi Literatur Riview Pengembangan Media Pembelajaran Articulate Storyline dalam Pembuatan Pola Dasar di Sekolah Menengah Kejuruan - Fatihaturrahmi Fatihaturrahmi; Dedy Irfan; Hansi Effendi (Departement of Mathematics Education, 2023)
Based on previous research studies on the subject of Making Clothing Patterns studied by students at Vocational High Schools for the Department of Fashion, the media that has been used in making basic patterns is still limited to the use of whiteboards and job sheets. This study aims to develop media design, determine the feasibility and student responses to interactive learning media based on Articulate Storyline on pattern making material. This study used a research and development (R&D) design in collaboration with media and material experts. The source of the data in this study is the validation results obtained from media experts and material experts and questionnaire data. The data obtained was then analyzed and presented in the form of data tabulations in tables and figures.